Między przeszłością a teraźniejszością. Idea emigracji na łamach „Dodatku Literacko-Naukowego” paryskiej „Syreny” 1954-1959 - Stobiecki, Rafał (Acta Universitatis Lodziensis. Folia Historica, 1998)
An idea of Polish emigration presented in the „Syrena” („Mermaid”) was turned towards the past in the double sense of the word. Its creatore were going to continue ideas of the XIXth century emigrants, as well as, they lived in the world of their values and dilemmas, which they regarded as their own. For these after-war emigrants, history was a kind of an escape from reality which was not acceptable. Noble ideas of legality and unity of the emigration had to lose where faced to troubles of everyday life and to reality of great politics. Attempts to transmit ideas of the XIXth century emigration to second half of the XXth century were unable to be successful.